Latihan Foot Massagese bagai penurunan tekanan darah pada pasien hipertensi di Desa Sukamulya - Ginanjar, Yoga; Rohman, Asri Aprilia; Zen, Dini Nurbaeti; Permana, Irfan; Agustin, Ervina Dwi; Devi, Fitria Kusuma (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Hypertension is a silent disease because people do not know they have hypertension before checking their blood pressure. The incidence of hypertension reaches 9.4 million deaths worldwide every year, the number of hypertension sufferers will continue to increase sharply and it is predicted that by 2025 around 29% of adults worldwide will suffer from hypertension. Objective: This service aims to train foot massage for hypertensive patients in an effort to reduce blood pressure Method: used in this activity uses several methods and stages consisting of the preparation stage and the activity stage. The preparation stage consists of preliminary studies, coordination with partners as well as preparation of the location and supporting media. The activity stage consists of pre-testing participants, taking blood pressure measurements Result: Based on the results of the training, it was found that there was an increase in knowledge with an average increase in post-test results of 17.2 with the highest score in the post-test being 100. Conclusion: There was a decrease in blood pressure in hypertensive patients after the intervention with an average decrease in respondents' blood pressure of 10 mmHg